1997
DOI: 10.1021/jf960734o
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of 2-(1-Hydroxyethyl)-2,4,5-trimethyl-3- oxazoline Formation under Low Temperature in 3-Hydroxy-2-butanone/Ammonium Acetate Model Systems

Abstract: Volatile compounds formed from the reaction of 3-hydroxy-2-butanone/ammonium acetate at 25, 55 and 85 °C were investigated. Six compounds were characterized by gas chromatography-mass spectrometry (EI and CI). Among the volatile compounds identified, an interesting intermediate compound, 2-(1-hydroxyethyl)-2,4,5-trimethyl-3-oxazoline, was found. 15 N-Labeled ammonium acetate was used to confirm the structure of 2-(1-hydroxyethyl)-2,4,5-trimethyl-3-oxazoline. The formation pathway of these volatile compounds wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…However, OXZ is unstable at high temperature and its reducing speed is highly dependent on temperature. As 2,4,5-trimethyl-3-oxazoline and 2,4,5-trimethyl-oxazole ( Figure 2) were not detected during this work, OXZ was postulated to transfer back to C 4 compounds ready for the condensation of TMP [18]. The fact that the purified OXZ product can slowly break down to form acetoin and TMP even it is stored in the dark at 4°C (data not shown) further supports this opinion.…”
Section: The Second Step: Accelerated Spontaneous Formation Of Tmpsupporting
confidence: 52%
See 2 more Smart Citations
“…However, OXZ is unstable at high temperature and its reducing speed is highly dependent on temperature. As 2,4,5-trimethyl-3-oxazoline and 2,4,5-trimethyl-oxazole ( Figure 2) were not detected during this work, OXZ was postulated to transfer back to C 4 compounds ready for the condensation of TMP [18]. The fact that the purified OXZ product can slowly break down to form acetoin and TMP even it is stored in the dark at 4°C (data not shown) further supports this opinion.…”
Section: The Second Step: Accelerated Spontaneous Formation Of Tmpsupporting
confidence: 52%
“…Acetoin can act as the precursors of many other kinds of compounds due to its reactive hydroxyl group and the hydrogens on the alpha position of the carbonyl group. Fu et al [18] revealed some side-reactions using GC-mass spectrometry (GC-MS) techniques. However, owing to the limitation of the gas chromatographic method, non-volatile derivatives may have been overlooked.…”
Section: Comparison Of Tmp Production Methods From Renewable Feedstocksmentioning
confidence: 99%
See 1 more Smart Citation
“…They have the same GC-EIMS spectra as shown in Figure 1. This mass spectrum matches well with the spectral data published previously by Shu and Lawrence (1995) and Fu and Ho (1997). They were, therefore, identified as syn and anti isomers of 2-(1-hydroxyethyl)-2,4,5-trimethyl-3-oxazoline.…”
Section: Resultssupporting
confidence: 89%
“…Thiazoles have also been found in various model systems involving either degradation of glucose in the presence of fragmentation of cysteine or cystine (Shu et al, 1885a,b) or reaction of these with reducing sugars (Kato et al, 1973) or furaneol (Shu and Ho, 1988). In recent studies on the reaction of 3-hydroxy-2-butanone with ammonium acetate at low tem-perature, an interesting compound, 2-(1-hydroxyethyl)-2,4,5-trimethyl-3-oxazoline along with 2,4,5-trimethyloxazole and 2,4,5-trimethyl-3-oxazoline, was isolated and identified (Shu and Lawrence, 1995;Fu and Ho, 1997). Our objective in the present study was to isolate and identify the oxazoles, oxazolines, thiazoles, and thiazolines from the reaction of 3-hydroxy-2-butanone and the ammonium sulfide model system.…”
Section: Introductionmentioning
confidence: 99%